Dominican Republic : Statistical Review of the Justice Sector - World Bank (Washington, DC, 2013)
This statistical review of the justice sector is the first study of its kind in the Latin America and the Caribbean region, and as such, is designed to promote further analytical work in other countries of the region. Through the application of statistical methods, it aims at responding to questions on the actual demand for judicial services, on the process of dispute resolution, and on judicial outcomes, and, through qualitative methods, the study explores the factors that facilitated, or hindered access to justice, in particular, access to the court system. Based on the available data, further analysis would be required before prescribing reforms. Nonetheless, findings suggest the need to better understand how the current structure, inhibits rather than enhances, access to justice. In fact, the overwhelming number of cases (petty, non-contentious, etc.) generates the crowding out of legitimate cases; indeed, the courts responsiveness limits access to those cases requiring the intervention of a judge. Regarding dispute resolution, current rules seemingly promote, and support behavioral patterns that cause delays, increase litigation costs, and exert the inefficient use of court resources, exemplified by minimal court fees, and inconsistent reimbursement fees, which decreases the costs associated with protracted litigation. Clearly patterns point at the need to examine, and improve the incentive structure, establish information systems, and judicial statistics, and, analyze further, and systematically the enforcement of judgments.